Decentralized and Multi-Objective Coordinated Optimization of Hybrid AC/DC Flexible Distribution Networks - Wang, Xiaoxue; Gu, Liting; Liang, Dong (Frontiers in Energy Research, 2021)
The increasing penetration of distributed energy resources and flexible electrical loads makes hybrid AC/DC distribution networks become a crucial trend for future modern distribution networks. To increase the flexibility and energy efficiency of hybrid AC/DC distribution networks, a decentralized and multi-objective coordinated optimization method by considering different control means is proposed. The salient feature of this method is that it comprehensively and properly models the full variety of possible control means (i.e., active/reactive power of distributed generation, on load tap changers, flexible distribution switch, voltage source converter). The abundant means are utilized to optimize operational cost, voltage deviation and network losses simultaneously. Then, a fully decentralized optimization method based on alternating direction multiplier method (ADMM) is proposed. The hybrid AC/DC distribution networks are divided into several sub-networks. Flexible interconnected electronic devices are utilized to transfer energy between different sub-networks to achieve the efficient and flexible utilization of controllable resources in hybrid AC/DC distribution networks. Finally, the proposed coordinated optimization method is tested on a modified dual IEEE 33-node network to demonstrate its effectiveness and advantages, and performance of the centralized method and our proposed method is compared.